Rio Ruidoso [large type] - Lewis, Preston (Lewis, Preston. Three rivers, 2021)
When Wes Bracken enters the Ruidoso Valley in 1873 for a fresh start raising horses with his alcoholic older brother, he finds himself ensnared in the crooked dealings of Lincoln County, New Mexico Territory. With saddle tramp Jace Cousins and the young newly-widowed mother Sarafina Zamora as steadfast allies, Bracken stands tall against lawlessness, whether corralling horse thieves, expelling the racist Horrell brothers, or challenging political kingpin Lawrence G. Murphy's economic stranglehold on the region.